Tertiary forestry education in Malaysia: current thinking and future direction - Awang, Kamis; Hadi, Yusuf; Majid, Nik Muhamad (Forestry Department Peninsular Malaysia, 1984)
The current programmes of instruction, research and extension at the Faculty of Forestry, Universiti Pertanian Malaysia are described and future directions of these programmes outlined. The degree and diploma programmes are designed to produce generalist-type foresters, with limited degree of specialization. The Faculty is in the process of preparing degree programmes to enable students to specialize in either forest management or wood industries, to cater for the requirements in the Malaysian forestry sector for specialists in the sector's effort to intensify forest management, improve log conversion processes and incorporate the wider uses of the forests. Research in the four thrust areas, namely hill forest management, plantation forestry, wood science and forest products, and forestry for the quality of life, is conducted with funds from the university and outside agencies. Extension activities have been intensified with the organizing of seminars, workshops, forums, short courses and other projects involving both staff and students.